2011
DOI: 10.1038/ismej.2011.18
|View full text |Cite
|
Sign up to set email alerts
|

Rapid shifts in picoeukaryote community structure in response to ocean acidification

Abstract: Rapid shifts in picoeukaryote community structure were observed during a CO 2 perturbation experiment in which we followed the development of phytoplankton blooms in nutrient-amended mesocosms under the present day or predicted future atmospheric pCO 2 (750 latm, seawater pH 7.8). Analysis of rbcL clone libraries (encoding the large subunit of RubisCO) and specific quantitative PCR assays showed that two prasinophytes closely related to Micromonas pusilla and Bathycoccus prasinos were present, but responded ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
44
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 40 publications
10
44
2
1
Order By: Relevance
“…A similar trend was observed a few years earlier at the same location, time of the year and experimental set-up, this time based on a M. pusilla-like flow cytometric signature (Engel et al, 2008). Meakin and Wyman (2011) showed that the picophytoplankter Bathycoccus (also belonging to the Prasinophyceae) was not affected by the increased CO 2 concentrations. Although we have no knowledge of the actual species that are represented by our flow cytometric clusters, our data show (1) the dominance of the picoeukaryotic phytoplankton in polar waters and (2) the potential ecological importance this group will have in future oceans.…”
Section: Phasesupporting
confidence: 78%
See 2 more Smart Citations
“…A similar trend was observed a few years earlier at the same location, time of the year and experimental set-up, this time based on a M. pusilla-like flow cytometric signature (Engel et al, 2008). Meakin and Wyman (2011) showed that the picophytoplankter Bathycoccus (also belonging to the Prasinophyceae) was not affected by the increased CO 2 concentrations. Although we have no knowledge of the actual species that are represented by our flow cytometric clusters, our data show (1) the dominance of the picoeukaryotic phytoplankton in polar waters and (2) the potential ecological importance this group will have in future oceans.…”
Section: Phasesupporting
confidence: 78%
“…Non-calcifying phytoplankton show, as expected, a range of responses, varying from no effect on growth to stimulating or adverse effect on growth or primary production (Riebesell and Tortell, 2011). Only a few studies have reported on OA-induced changes of phytoplankton community composition (Tortell et al, 2002, Engel et al, 2008Meakin and Wyman, 2011;Feng et al, 2009), and the ecological consequences of OA on natural phytoplankton dynamics are still understudied.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…This finding is in line with previous studies, which have shown that picoeukaryotes can benefit 334 strongly from OA in both laboratory and mesocosm studies (Meakin and Wyman, 2011;335 Newbold et al, 2012;Schaum et al, 2012;Brussaard et al, 2013;Maat et al, 2014;Schulz et 336 al., 2017). Such positive response to OA could indicate that picoeukaryotes such as M. pusilla 337 are mainly dependent on diffusive CO 2 supply and thus directly benefit from higher CO 2 338 concentrations Schulz et al, 2013;Schulz et al, 2017).…”
Section: Micromonas Pusilla Benefits From Warming 296supporting
confidence: 89%
“…have shown picoeukaryotes, particularly M. pusilla, to increase in relative abundance with 62 increasing pCO 2 levels (Engel et al, 2008;Meakin and Wyman, 2011;Newbold et al, 2012;63 Brussaard et al, 2013;Schulz et al, 2017). Despite the evident sensitivity of M. pusilla to 64 changes in pCO 2 levels, a detailed assessment of the OA effects, their interaction with warming 65 as well as the underlying mechanisms in this important species is still missing.…”
Section: Introduction 28mentioning
confidence: 99%